Negotiations in the Oil Investment Contract - Kadhim, Dhurgham Mahmood (International Journal of Psychosocial Rehabilitation, 2020)
The conclusion of our research (negotiations in the oil investment contract) is that this is a type of contract that is often characterized by unequal contractual parties. The (foreign) investor is always in a position that allows him to impose his contractual conditions in the interests of the investing state. In view of the importance of these contracts, which have gained their luck in the field of legal studies, both the producing countries and the investing parties have tended to change these contracts in a manner that insures them continuing production with greater returns, so the producing countries are often the demanding party trying to extract their rights from the exploiting companies by various means. Chief among them is the possibility of giving interpretations of some contract texts in its favor or trying to replace some texts under the pretext that the conditions of their contract have changed, and other reasons that require these countries, which are mostly developing countries, an attempt to find the largest amount to achieve their economic interests, there are controls that determine the relations of countries with foreign companies Investing in oil, which is linked to the economic goals of countries, and that these goals may or may not coincide with the goals of these companies. From here came the importance of our discussion of negotiations as one of the means of oversight in the oil investment contract, as jurisprudence divides control into a precedent and subsequent, as well as internal and external, and also divides it into prohibitive and revealing, as for the Iraqi Companies Law, it shows through Chapter Five, the control tools and the requirements Necessary to exercise control, as well as administrative and financial control. Which raises the question about the main objectives of the existence of companies investing in oil? And is the presence of these companies in the host countries based on the balance between achieving profit and not harming the economic interests of the oil-producing countries, which necessitated that we divide the study into two topics, the first of which was devoted to us: to clarify the negotiating stage of the oil investment contract, and the second topic: it was devoted to a statement of responsibility and a penalty Breach of negotiations.